A Synthesis of Sloan-C Effective Practices, November 2010 - Moore, Janet C. (Online Learning, 2010)
Encouraging continuous improvement in the quality, scale and breadth of online education, the Sloan Consortium invites practitioners to share effective practices. This report synthesizes effective practices submitted by Sloan-C members to the online collection at http://www.sloanconsortium.org/effective as of November 2010. The synthesis includes links to the provider institutions and to detailed postings about practices.